Using different potassium and magnesium treatments in watermelon production - Böhm Viktória (Review on agriculture and rural development, 2012)
Since watermelon yield and quality are so greatly influenced by production practices, it is important that watermelon varieties be tested under adequate nutrition conditions. This study was conducted in 2009 and 2011 in county Békés. Watermelon cultivar Crisby was used in both year, furthermore in 2009 besides the non-grafted plants we used 2 grafted combinations, with the following rootstocks: Strongtosa (interspecific squash hybrid) and Nun 3001 (Lagenaria type). Plants were grown under low tunnel conditions with intensive technology (soil covering, dripp-irragtion). 4 fertilization treatments were used with different potassium dose. In every treatment half of the plants got foliar magnesium fertilizer (EpsoMicrotop), applied in concentration of 5%. The measurement of the yield and fruit weight (kg, average mass) were carried out in the field, while the fruit quality analyses (dry matter content, soluble solid content (Brix%), sugar content) were taken place in laboratory. In 2009 our results showed that interspecific rootstock gave higher yield and with higher potassium dozen the fruit quality won’t be decreased. In 2011 the yield and TSS content was parallel with the increasing potassium doses. In both year the effect of the magnesium foliar fertilizer was more remarkable by lower potassium doses.